2015
DOI: 10.1007/s11666-015-0251-1
|View full text |Cite
|
Sign up to set email alerts
|

Titanium Dioxide Coating Prepared by Use of a Suspension-Solution Plasma-Spray Process

Abstract: Titanium dioxide coatings were prepared from titanium isopropoxide solution containing nano TiO 2 particles by use of a plasma-spray process. The effects of stand-off distance on coating composition and microstructure were investigated and compared with those for pure solution precursor and a water-based suspension of TiO 2 . The results showed that the anatase content of the coating increased with increasing stand-off distance and the rate of deposition decreased with increasing spray distance. Anatase nanopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 44 publications
0
9
0
1
Order By: Relevance
“…The photocatalytic activity of TiO 2 coatings depends strongly on their phase composition and microstructure. Many techniques have been employed to tailor these properties of TiO 2 , which include sol–gel methods [ 3 ], spray pyrolysis [ 4 ], chemical vapor deposition (CVD) [ 5 ], cold spraying [ 6 ], high-velocity oxy-fuel (HVOF) [ 7 ], and plasma spraying processes [ 8 , 9 , 10 ]. Among these methods, the plasma spraying process is on the cutting edge of flexible and high-rate deposition, in which the thickness and morphology can be precisely controlled [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The photocatalytic activity of TiO 2 coatings depends strongly on their phase composition and microstructure. Many techniques have been employed to tailor these properties of TiO 2 , which include sol–gel methods [ 3 ], spray pyrolysis [ 4 ], chemical vapor deposition (CVD) [ 5 ], cold spraying [ 6 ], high-velocity oxy-fuel (HVOF) [ 7 ], and plasma spraying processes [ 8 , 9 , 10 ]. Among these methods, the plasma spraying process is on the cutting edge of flexible and high-rate deposition, in which the thickness and morphology can be precisely controlled [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many techniques have been employed to tailor these properties of TiO 2 , which include sol–gel methods [ 3 ], spray pyrolysis [ 4 ], chemical vapor deposition (CVD) [ 5 ], cold spraying [ 6 ], high-velocity oxy-fuel (HVOF) [ 7 ], and plasma spraying processes [ 8 , 9 , 10 ]. Among these methods, the plasma spraying process is on the cutting edge of flexible and high-rate deposition, in which the thickness and morphology can be precisely controlled [ 10 , 11 ]. Specifically, solution precursor plasma spraying (SPPS) was introduced to obtain coatings with micro- and nano-scale structural features.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actualmente hay un interés creciente para el desarrollo de materiales que posean suficiente fotosensibilidad y puedan ser útiles para la resolución de problemas ambientales (Gora et al 2018, Lu et al 2018, Maghsoodi et al 2019, Yao et al 2020). El TiO 2 es un fotocatalizador ampliamente utilizado, ya que tiene ventajas como bajo costo, ausencia de toxicidad y estabilidad química; además, es adecuado para el tratamiento de contaminantes orgánicos en aire y agua como colorantes, fármacos, compuestos orgánicos clorados, compuestos fenólicos y herbicidas, entre otros (Du et al 2015, Khatibnezhad y Faghihi-Sani 2015, Chen et al 2016, Bagheri et al 2017, Odling et al 2018, Peleyeju y Arotiba 2018. El TiO 2 se activa mediante irradiación ultravioleta, generando el transporte de cargas del par electrón-hueco, las cuales son altamente oxidantes de contaminantes orgánicos.…”
Section: Introductionunclassified
“…The resulting coating microstructure highly depends on the history of the droplets inside the plasma and therefore the plasma parameters. For example, it has been shown that the precursor concentration and the solvent type have a strong influence on the porosity of the coating [5]- [8], while spraying distance and power played a role on the phase composition [7], [9]. As such, achieving a better control of SPPS requires a thorough understanding of these mechanisms.…”
Section: Introductionmentioning
confidence: 99%